Two new species of Torunotum Hosseini & Cassis 2019 (Hemiptera: Miridae: Deraeocorinae: Hyaliodini) from New Caledonia - Gierlasiński, Grzegorz; Dobosz, Roland; Taszakowski, Artur (Zootaxa, 2024)
Two new species of the Torunotum Hosseini & Cassis, 2019—T. hirsutum sp. nov. and T. flavomaculatum sp. nov.—are diagnosed and described. Photographic images of habitus and male genital structures, as well as scanning electron micrographs of the selected structures of these species, are provided. Additionally, the paper also presents a new locality of Torunotum badius Hosseini & Cassis, 2019, along with photographs of the habitus and the male genitalia.